Audit judgment through time budget pressure, quality of sleep, and ego depletion - Yustina, Andi Ina; Aritonang, Elisha Princess Christin Natalia; Andrianantenaina, Hajanirina (Jurnal Akuntansi dan Auditing Indonesia, 2023)
This study aims to investigate whether time budget pressure, sleep quality, and ego depletion affect the quality of audit judgment. A quantitative approach was used to collect data from 100 auditors working in both Big Four and Non-Big Four accounting firms. We tested the hypothesis using the Sequential Equation Model-Partial Least Squares (SEM-PLS) technique. The results of this study showed that time budget pressure and sleep quality do not have a significant impact on audit judgment. However, ego depletion has a negative impact on audit judgment. These findings can be beneficial in two ways. Firstly, the study provides an early warning to the human resources department or partner of a public accounting firm about the current phenomenon among auditors. Secondly, other researchers who are interested in exploring factors influencing audit judgment during the high season or peak season can benefit from this study.